2012
DOI: 10.1177/0160323x12439214
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Possibilities for Regional Collaboration among Small Jurisdictions

Abstract: This research note examines the Western Wisconsin Intergovernmental Collaborative (WWIC), located in three mainly rural Wisconsin counties bordering the Minneapolis–St. Paul region, including the results of a survey of chief elected officials representing local governments in the region. Despite the fact that the WWIC has not generated significant interest among most prospective member governments, survey results indicate that many of these governments are engaged in collaborations with other jurisdictions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…, 2013, 2019; Zeiner and Tjerbo, 2014). Previous research supports this distinction (Folz and Abdelrazek, 2009; Kraus, 2012; Visser, 2004; Warner and Hefetz, 2008), as CAOs in small USA cities possess a broader selection of informal collaborative alternatives, such as special districts, nonprofits and private business, due to the generality and commonality of service objectives.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…, 2013, 2019; Zeiner and Tjerbo, 2014). Previous research supports this distinction (Folz and Abdelrazek, 2009; Kraus, 2012; Visser, 2004; Warner and Hefetz, 2008), as CAOs in small USA cities possess a broader selection of informal collaborative alternatives, such as special districts, nonprofits and private business, due to the generality and commonality of service objectives.…”
Section: Discussionmentioning
confidence: 88%
“…, 2020). Size may also be instrumental, as smaller municipalities tend to favor more informal arrangements (Fowler, 2018; Kraus, 2012). The political atmosphere, forces of political culture (Elazar, 1972) and the inclinations of elected officials and other stakeholders (Sonderskov, 2019) likewise affect the aptitude for collaboration and the mechanism options available to managers (Swann, 2015).…”
Section: Ilc Mechanisms and Management In The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Lack of collaboration is due to lack of interest; this is indeed the fastest conclusion, but the real work to be done is to dig for true reasons behind lack of interest [20]. Here we find trust, different level of knowledge and expertise level, insufficient information about the personal impact through involvement, etc.…”
Section: Culture Of Collaborationmentioning
confidence: 83%
“…Conversely, the more formal and specific mechanisms, namely consortiums, contracts, and joint ventures, were commonly used for program conglomerations such as energy distribution and law enforcement. According to recent research, this shift to informality may signal preference for a more autonomous approach toward collaboration, independent of aggregated corporations, especially among smaller communities (Kraus 2012). It may also signify the desire for more regionally based cooperation, as was indicated in the common understandings, agreements, and federations of Nebraska case studies, and in-house provision options such as demonstrated in the Gretna contract situation.…”
Section: Findings and Discussionmentioning
confidence: 99%